Surveying and Mapping in Nepalese Context - Pradhananga, Tirtha Bahadur (Journal on Geoinformatics, Nepal, 2007)
Surveying and mapping is indispensable for the development of any country. In our context, the history of the development of surveying and mapping is gradually marching with the pase of global technological development. This paper explores the various components of Surveying and Mapping history and activities in Nepal e.g. Cadastral, Geodetic, Topographical, HRD, Land Use, NGIIP, DoLIA.